Thermotropic liquid crystalline polyesters derived from 2-chloro hydroquinone - Manurkar, Nagesh; More, Sayaji; Mulani, Khudbudin; Ganjave, Nitin; Chavan, Nayaku (Journal of Chemical Sciences, 2017)
Synthesis of thermotropic liquid crystalline polyesters derived from bis[4-hydroxy benzoyloxy]-2-chloro-1,4-benzene (BHBOCB) and aliphatic dicarboxylic acid chlorides by interfacial polycondensation methodology is presented. Synthesised polyesters consist of bis[4-hydroxy benzoyloxy]-2-chloro-1,4-benzene as a mesogen and aliphatic diacid chloride as flexible spacer. The length of oligomethylene units in the polymer was varied from the trimethylene to the dodecamethylene groups. Synthesized polyesters were characterized by differential scanning calorimetry and optical microscopy. The transition temperatures and thermodynamic properties were studied for all these polymers. These polyesters exhibited thermotropic liquid crystalline behavior and showed nematic texture except decamethylene spacer. Decamethylene spacer based polyester showed marble texture of smectic C. Mesophase stability of these polyesters was higher than (except first heating cycle of PE-1).  SYNOPSIS The present study deals with the synthesis of thermotropic liquid crystalline polyesters derived from bis[4-hydroxy benzoyloxy]-2-chloro-1,4-benzene (BHBOCB) and aliphatic dicarboxylic acid chlorides by interfacial polycondensation methodology.
Keywords: acid; Aliphatic Flexible Spacers Main-chain; Aromatic Mesogen; Elastomer; Morphology; Polydomain; Polymers; Thermotropic Liquid Crystalline Polyesters; Units

Adsorptive removal of chromium(VI) using spherical resorcinol-formaldehyde beads prepared by inverse suspension polymerization - Mulani, Khudbudin; Patil, Vishwanath; Chavan, Nayaku; Donde, Kamini (Journal of Polymer Research, 2019)
The spherical cross-linked beaded polymers were prepared by condensation of resorcinol and formaldehyde in presence of tri-ethylamine by inverse suspension polymerization technique. The m-cresol, aniline, urea and thiourea were used as co-monomer and polyethylene glycol (PEG 400) was used as porogen. Paraffin oil was used as non-aqueous suspension agent. The polymeric spherical beads were prepared using various types of comonomers exhibiting range of particle size 77.62 to 158.84m at 90 degrees C and 300rpm for 4h. The resulting beads were analyzed by elemental analysis, particle size analysis and scanning electron microscope (SEM). The synthesized beads were used for the removal of Cr(VI) from aqueous solutions. A simple and sensitive solid phase extraction procedure was used for the determination of chromium at trace level by spectrophotometric method using 1,5-diphenylcarbazide reagent. The adsorption of Cr(VI) on the resorcinol-formaldehyde beads was monitored by energy-dispersive X-ray spectroscopy (EDX) analysis. The metal adsorption parameters such as contact time, pH, metal ion concentration and adsorbent dose were investigated. For Cr(VI), the maximum adsorption capacity was about 99% at pH2 for the resorcinol-formaldehyde beads obtained.
Keywords: adsorption kinetics; Beads; Chromium (VI); Formaldehyde; Inverse suspension; Resorcinol

Construction of beta-cyclodextrin linked glycidyl methacrylate polymers for stereoselective separation of chiral drug - Wale, Apparav; Mulani, Khudbudin; Deshpande, Supriya; Rajan, C. R.; Ponrathnam, Surendra (Journal of Polymer Research, 2021)
In this present study, a series of cross-linked porous polymers based on Glycidyl Methacrylate (GMA) were synthesized by suspension polymerization using cyclohexanol and hexanol as pore generating solvents. beta-cyclodextrin (beta-CD) was covalently bonded to the polymers by using Hexamethylene Diisocyanate (HMDI) and Sebacoyl Chloride (SC) as spacer arms. The effects of matrix properties such as pore volume, type of crosslinker, and spacer on the loading of beta-cyclodextrin were investigated. The stereoselective binding of enantiomers of the anti-depressant drug citalopram was studied using beta-cyclodextrin loaded polymers under batch adsorption mode. The capacity factor and selectivity of isomers were investigated also. This study reveals that these beta-cyclodextrin bonded Glycidyl Methacrylate (GMA) polymers are potentially suitable for chromatographic separation of citalopram.
Keywords: beta-cyclodextrin; Citalopram; Glycidyl Methacrylate (GMA) beads; HPLC etc; Stereoslelctivity